Contract law - Andrews, Neil (Cambridge University Press, 2015)
"Significantly streamlined and updated, the second edition of Andrews' Contract Law now provides a clear and succinct examination of all of the topics in the contract law curriculum. Chapters direct students to the most important decisions in case law and employ a two-level structure to integrate short judicial excerpts into detailed discussion and analysis. Exploration of the law's 'loose ends' strengthens students' ability to effectively analyse case law, and new end-of-chapter questions, which focus on both core aspects of the law and interesting legal loopholes, assist students in preparing for exams. Students are guided through chapter material by concise chapter overviews and a two-colour text design that highlights important chapter elements. Suggestions for further reading and a rich bibliography, which point readers to important pieces of contemporary literature and provide a springboard for deeper investigation of particular topics, lend further support for student learning"--